Neuroimaging markers and disability scales in multiple sclerosis: A systematic review and meta-analysis - Mirmosayyeb, Omid; Yazdan Panah, Mohammad; Mokary, Yousef; Mohammadi, Mohammad; Moases Ghaffary, Elham; Shaygannejad, Vahid; Weinstock-Guttman, Bianca; Zivadinov, Robert; Jakimovski, Dejan (PloS one, 2024)
Multiple sclerosis (MS) is a central nervous system disorder marked by progressive neurological impairments. Magnetic resonance imaging (MRI) parameters are key paraclinical measures that play a crucial role in the diagnosis, prognosis, and monitoring of MS-related disability. This study aims to analyze and summarize the existing literature on the correlation between MRI parameters and disability in people with MS (pwMS). The PubMed/MEDLINE, Embase, Scopus, and Web of Science databases were searched from inception to July 19, 2024, and a meta-analysis was carried out using R software version 4.4.0 and the random effects model used to determine the pooled correlation coefficient, with its 95% confidence interval (CI), between MRI measurements and disability scales. Among 5741 studies, 383 studies with 39707 pwMS were included. The meta-analysis demonstrated that Expanded Disability Status Scale (EDSS) had significant correlations with cervical cord volume (r = -0.51, 95% CI: -0.62 to -0.38, I2 = 0%, p-heterogeneity = 0.86, p-value<0.01), cortical lesion volume (r = 0.45, 95% CI: 0.36 to 0.53, I2 = 68%, p-heterogeneity<0.01, p-value<0.01), brain volume (r = -0.40, 95% CI: -0.47 to -0.33, I2 = 41%, p-heterogeneity = 0.05, p-value<0.05), and grey matter volume (GMV) (r = -0.36, 95% CI: -0.49 to -0.21, I2 = 0%, p-heterogeneity = 0.53, p-value<0.01), respectively. This study offers evidence suggesting that cortical lesion volume, brain volume, GMV, and MRI measurements of the spinal cord may constitute reliable indicators for assessing disability in pwMS.